Gracilis Muscle Flap After Superficial Inguinal Lymphadenectomy in an Irradiated Inguinal Field. Issue 4 (April 2023) - Valenzuela, Cristian D.; Finlay, David; Sabry, Zakir; Mariadason, James G.; Wallack, Marc K.
The sartorius muscle transposition flap is the traditional method of femoral vessel coverage after superficial inguinal lymphadenectomy for regionally-metastatic cancers to the inguinal lymph nodes. However, if the groin has undergone radiotherapy, the sartorius muscle is contained within the irradiated field, and may be problematic for wound healing, in addition to being thin at its insertion and intimately related to several nerves. The gracilis muscle has been used for soft tissue defects and vascular graft infections, but its utility as an alternative to the sartorius muscle flap in the setting of radiation has never been reported. Here, we report the successful use of the retroflexed gracilis muscle flap for femoral vessel coverage after superficial inguinal lymphadenectomy, in a patient who previously underwent chemoradiation for locally-metastatic anal squamous cell carcinoma to the groin. An 86-year old female presented with Stage IIIB anal squamous cell carcinoma metastatic to one left inguinal lymph node. She underwent modified Nigro protocol chemoradiation treatment, which included radiation to the inguinal node basins. A left superficial inguinal lymphadenectomy was performed with a retroflexed gracilis muscle flap to cover the femoral vessels. This was chosen over a sartorius flap because the gracilis muscle was not located within the field of radiation. Despite a subsequent groin wound infection, the gracilis muscle flap remained viable and successfully protected the major vessels. We report the gracilis muscle flap as a viable alternative to the sartorius transposition muscle flap for femoral vessel coverage after oncologic superficial inguinal lymphadenectomy in the irradiated groin.